2016
DOI: 10.1097/scs.0000000000002835
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Tranexamic Acid Protocol to Reduce Blood Loss During Cranial Vault Remodeling for Craniosynostosis

Abstract: The introduction of TXA for nonsyndromic single-suture synostosis repair at our institution has significantly reduced blood loss and blood product and plasma transfusion during and following primary cranial vault remodeling for single suture craniosynostosis. Postoperative hematocrit was similar in the TXA-treated and untreated groups despite reduced red cell transfusion in the treated group. In addition, TXA use in this population has eliminated the need for plasma transfusion, and is associated with a shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 7 publications
0
52
0
Order By: Relevance
“…19 On the other hand, a single-center, retrospective review of 259 patients before and after implementation of a TXA protocol found that TXA was not associated with higher postoperative hemoglobin, but significantly reduced intraoperative transfusion requirements. 20 Additionally, a single-center, retrospective study of pre-and postimplementation of postoperative furosemide administration in CVR patients found a significant reduction in transfusion rates. 21 The use of furosemide was implemented because the perceived anemia was thought to be mostly attributable to hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…19 On the other hand, a single-center, retrospective review of 259 patients before and after implementation of a TXA protocol found that TXA was not associated with higher postoperative hemoglobin, but significantly reduced intraoperative transfusion requirements. 20 Additionally, a single-center, retrospective study of pre-and postimplementation of postoperative furosemide administration in CVR patients found a significant reduction in transfusion rates. 21 The use of furosemide was implemented because the perceived anemia was thought to be mostly attributable to hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies were eligible for our review. Of the 13 studies, 4 were prospective, randomized, double-blind controlled trials [9,10,14,15], 9 were retrospective studies, tailored as a "before-after" studies, comparing blood loss and transfusion without/with TXA [16][17][18][19][20][21][22][23][24]. Study characteristics are presented in Table 1 and 2.…”
Section: Selection Of Reports and Study Designmentioning
confidence: 99%
“…A loading dose was commonly used, with doses ranging from 10 mg/kg [14,15,18,[20][21][22] to 100 mg/kg [16], usually infused over 15 minutes after induction of general anesthesia and before skin incision. A continuous infusion until skin closure was performed in all studies, with different protocols: 5 mg/kg/h [10,14,18,[20][21][22][23] or 10 mg/kg/h [9,16,17,19,24].…”
Section: Analysis Of Protocolsmentioning
confidence: 99%
See 2 more Smart Citations